Rethinking health accountability in Mozambique: Beyond donors and government? (Institute of Development Studies, 2018)
As I explored in my previous blog, the health sector and provision of health services in Mozambique is an uneven playing field. Since 1980 it has been shaped by a range of donors who have strategically positioned themselves according to their political weight and ability to contribute with ‘commodities’ and financial resources.  Although donors’ contributions […]
Keywords: G - Mozambique / Moçambique; L - english / inglês; accountability / responsabilização; health / saúde

Making Information Disclosure in Extractive Governance Count for Accountability in Mozambique - Awortwi, Nicholas; Nuvunga, Adriano (Partnership for African Social and Governance Research (PASGR), 2018)
A recent study on information disclosure in the extractive sector has found 18 factors that result in citizen and institutional (state and non-state) inaction in demanding government accountability. Conducted by the Partnership for African Social and Governance Research (PASGR) in collaboration with the Centre for Public Integrity (CIP), as part of the Action for Empowerment and Accountability (A4EA) research programme, the study shows that citizens and/or institutions are unlikely to demand government accountability when: • citizens’ are experiencing high levels of economic vulnerability but much of the access to economic opportunities are anchored around state patronage and network; • a single political party has dominated governments for a long period of time and the mode of selection of Parliamentarians is defined by a ‘party list’, and not directly elected by the people; • CSOs have weak citizens’ mobilisation strategies and information disclosure is presented in a written form in a context where adult illiteracy rate is 45%; • there is an institutional culture of ‘submissiveness’ created out of fear of the political regime
Keywords: G - Mozambique / Moçambique; L - english / inglês; accountability / responsabilização; extractive industries / indústrias extractivas

Inverted State and Citizens’ Roles in the Mozambican Health Sector - Dias, Jose; Tomé, Tassiana (IDS Bulletin, 2018)
This article aims to understand the inversion of roles between the state and citizens, by exploring its historical roots and current implications for processes of social accountability in Mozambique, particularly in the health sector. This is a practice-based reflection grounded in the evidence collected through the implementation of Community Scorecards in the health sector in 13 districts of Mozambique. The evidence has revealed a transfer of responsibilities from local governance institutions and service providers to the communities; diluting the frontiers between the state and citizens’ duties and rights, resulting in the inversion of roles. This inversion results in the minimisation of the state’s performance of its duties and accountability in the health sector to respond to local communities’ needs, allegedly due to the lack of financial resources. It also leads to the overburdening of local communities, who assume the responsibility of meeting their own demands, risking participation fatigue.
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; Important; L - english / inglês; Northern PEA; accountability / responsabilização; health / saúde